(untitled) (Bulletin of the Taras Shevchenko National University of Kyiv. Chemistry, 2019)
Antimony and its compounds are widely used in industry, making it one of the priority pollutants of air and the aquatic environment. Excess of antimony is selectively concentrated in a thyroid gland, a liver, a spleen. The manifestation of the toxic effect of antimony is a variety of impaired functions of the human body, so the content of this element in drinking water normalizes is at the level of 5 μg/l. Recently, tellurium has also been increasingly the subject of research by analyst chemists. Tellurium is a biologically active element and its concentrations in the environment are strictly regulated. According to sanitary rules and regulations, the maximum allowable concentration of tellurium in drinking water is 0.01 mg/l. The article is devoted to the elaboration of solid-phase reagents based on the quaternary ammonium salt (QAS) immobilized on silica gel and to the development on this basis of sorption-spectrometric and visual test-methods of the determination of Sb(III) and Te(IV). The mechanism of the interaction between QAS immobilized on silica gel and the anions iodide complex of antimony and tellurium was studied. It was found that it proceeds by the ion-associative mechanism. Conditions of sorption preconcentration of anionic complexes of elements were optimized. For the quantitative sorption of antimony (III), the weight of the sorbent is 0.020 g and the volume of the solution is 25.0 ml. Under these conditions, the anionic complex is sorbed by 98 %. The maximum concentration ratio is 1.25 l/g. The sorption equilibrium in the system is established in 20 minutes. For the quantitative extraction of tellurium (IV), the optimal weight of the sorbent is 0.050 g and a solution volume of 25.0 ml. Under these conditions, the degree of sorption reaches about 80 %. The maximum concentration ratio is 0.4 l/g. The sorption equilibrium in the system is established in 15 minutes. The influence of foreign ions on the extraction degree of the investigated elements, and also on the magnitude of analytical signal, was studied. Sorption-spectrometric and visual test-methods of the determination of Sb(III) and Te(IV) in pharmaceutical preparation "Antimonium tartaricum" and "Tellurium Metalicum"